Espaço fílmico urbano : um retrato da área de interesse nas interseções entre cidade e cinema - Cavalcanti, Andrei de Ferrer e Arruda (2024)
This thesis starts from the premise that there is substantial and lasting interest in the interactions between built space and cinema, which justifies an epistemological reflection on the subject. Despite abundant literary production over more than a century, few studies offer significant contributions in this regard, resulting in a dispersed, repetitive, and often superficial bibliography. To propose an autonomy centered in the field of architecture and urbanism, which is often eclipsed by approaches from other humanities disciplines, an organizational effort was undertook, drawing from a wide range of works in which were identified the elements that Jairo Borges-Andrade (2003) expects to be consolidated in a research line, including its boundaries, direction, concepts, and procedures. This approach involves the establishment of a focus on the representation of urban space in narrative films, exploring its formal qualities; a historiographical investigation of the discourse on the relationships between built space and cinema; the definition of the concept of filmic space and its various categories; and the compilation of analytical procedures that can equip researchers to interpret the communicative aspects of urban filmic space.